Coming to terms with not coming : meanings, lived realities, & sexual identities of young women - Masagoes Agoes, Masayoe Nabilah (2018)
Even in a contemporary, postfeminist environment of heightened sexual awareness and liberty, the orgasm gap persists to plague heterosexual women in their penetrative sexual intercourse experiences. Yet, relatively little social science research has inquired how women, particularly young women, make sense of and around sexual pleasure, and how these meanings influence their identities as sexual beings. This study aimed to provide a rich exploration of the meanings and practices surrounding orgasm during sex with an intimate other, drawing upon qualitative data gathered from in-depth interviews with 12 sexually experienced young women. A feminist poststructuralist discourse functioned as a framework to identify and explore patterns derived from participants’ narratives, in a manner that prioritises the interpretations and understandings of their experiences. Themes extracted from the data follow participants’ meaning-making from their initial attitudes towards entitlement of sexual pleasure, awareness and appreciation of the lived realities of sex, to the discursive strategies employed to attain sexual satisfaction. Findings demonstrate the complex and contextual nature of orgasm, and how this influences women’s understandings of what it means to be both a sexual individual and sexual partner.